Aplicación de un sistema contable en la MC ubicada en la parroquia Lasso, cantón Latacunga, provincia de Cotopaxi por el año fiscal 2019. - Gualotuña Atupaña, Joselyn Andreina (2020)
The main objective of the research work is the application of an accounting system in the MC Hardware Store for 2019 year. It is a feasible project because it proposes a solution to the lack of an accounting software for the administration and control of the commercial and administrative activities of the company. The research problem was developed with an exploratory field research carried out at the hardware store and a descriptive research focused on the collection of necessary information. In addition, to describe the procedures, the qualitative method was used which was useful to know the general information. Also, the quantitative method was used because the accounting processes were studied and the financial statements were presented at the end of the accounting year. Observation was used as a research technique because it facilitated the application of interviews with the owner and staff of the company, achieving a clear idea of the economic situation in which it was located. Some activities were made as; the process of application of the accounting system that detailed the organizational structure, mapping of processes of each function made in the hardware store, plan of accounts elaborated by the investigators, inventory of merchandise, catalogue of products, parameterization of the accounting software that covered fundamental information for the correct operation, being able to visualize the benefits of the project with an improvement in the inventories and as well allowing to have an exact and detailed control of inventories. Finally, Financial Statements obtention for the 2019 period in the SACI accounting software improved administrative performance for decision making. The most relevant impact generated by the integration project is the social impact because it met the expectations and needs of customers in the area and at the same time it helps the hardware store become a great commercial outlet.